This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Economics 204 Lecture 5Friday, August 4, 2006 Revised 8/7/06, revisions marked by ** Section 2.6 (Continued) Properties of Real Functions Theorem 1 (6.23, Extreme Value Theorem) Let f be a continuous realvalued function on [ a, b ] . Then f assumes its minimum and maximum on [ a, b ] . In particular, f is bounded above and below. Proof: Let M = sup { f ( t ) : t [ a, b ] } If M is finite, for each n , we may choose t n such that M f ( t n ) M 1 n (if we couldnt make such a choice, then M 1 n would be an upper bound and M would not be the supremum). If M is in finite, choose t n such that f ( t n ) n . By the BolzanoWeierstrass Theorem, { t n } contains a convergent subsequence { t n k } , with lim k t n k = t [ a, b ] Since f is continuous, f ( t ) = lim t t f ( t ) = lim k f t n k = M so M is finite and f ( t ) = M = sup { f ( t ) : t [ a, b ] } so f attains its maximum and is bounded above. The argument for the minimum is similar. 1 Theorem 2 (6.24, Intermediate Value Theorem) Suppose f : [ a, b ] R is continuous, and f ( a ) < d < f ( b ) . Then there exists c ( a, b ) such that f ( c ) = d . Proof: We did a handson proof already. Now, we can simplify it a bit. Let B = { t [ a, b ] : f ( t ) < d } a B , so B 6 = . By the Supremum Property, sup B exists and is real so let c = sup B . Since a B , c a . B [ a, b ], so c b . Therefore, c [ a, b ]. We claim that f ( c ) = d . Let t n = min c + 1 n , b Either t n > c , in which case t n 6 B , or t n = c = b , in which case f ( t n ) > d , so again t n 6 B ; in either case, f ( t n ) d . Since f is continuous at c , f ( c ) = lim n f ( t n ) d (Theorem 3.5 in de la Fuente). Since c = sup B , we may find s n B such that c s n c 1 n Since s n B , f ( s n ) < d . Sinc e f is continuous at c , f ( c ) = lim n f ( s n ) d (Theorem 3.5 in de la Fuente). Since d f ( c ) d , f ( c ) = d . Since f ( a ) < d and f ( b ) > d , a 6 = c 6 = b , so c ( a, b ). Monotonic Functions: Definition 3 A function f is monotonically increasing if y > x f ( y ) f ( x ) 2 Theorem 4 (6.27) Suppose f is monotonically increasing on ( a, b ) . Then the onesided limits f ( t + ) = lim s t + f ( s ) f ( t ) = lim s t f ( s ) exist and are real numbers for all...
View
Full
Document
 Summer '08
 Staff
 Economics

Click to edit the document details